High-performance copper alloy and preparation process thereof

By adopting smelting and casting, solid solution treatment, cold rolling and two-time aging treatment processes on Cu-Cr-Zr alloys, the problem of difficult alloys in the prior art is to achieve high strength and high conductivity at the same time, and a significant improvement in conductivity, Vickers hardness and tensile strength has been achieved, and its application in high-end fields has been expanded.

CN119800255AInactive Publication Date: 2025-04-11鹤山市金益铜业有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510023037.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the high strength and high conductivity of Cu-Cr-Zr alloys simultaneously, especially in terms of tensile strength, which cannot meet the expected requirements, limiting its wide application in high-end fields.

Method used

A process including smelting and casting, solid solution treatment, cold rolling and two aging treatments is used. The specific steps include: performing a solid solution treatment of 60-120 minutes at 900-960°C, followed by 40-80% cold rolling deformation, and performing primary and secondary aging treatments at 150-160°C and 440-560°C respectively.

Benefits of technology

Through this process, the conductivity of Cu-Cr-Zr alloy reaches ≥79%, the Vickers hardness reaches ≥148, and the tensile strength reaches ≥584MPa, which significantly improves its comprehensive performance and makes it more widely used in the fields of electricity, electronics, machinery, etc.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of alloys, in particular to a high-performance copper alloy and a preparation process thereof. The preparation process of the high-performance copper alloy comprises the following steps that S1, smelting and casting are conducted, specifically, an alloy ingot with the expression of Cu-Crx-Zry is obtained, x is equal to 0.5-0.7, and y is equal to 0.1-0.19; s2, solid solution treatment is conducted, specifically, the alloy ingot is subjected to solid solution treatment for 60-120 min at the temperature of 900-960 DEG C, and the solid solution heating rate is 8-15 DEG C / min; s3, cold rolling, wherein the cold rolling deformation is 40-80%; and S4, aging is conducted, specifically, the treatment temperature of first-stage aging ranges from 150 DEG C to 160 DEG C, the treatment time ranges from 250 min to 350 min, the treatment temperature of second-stage aging ranges from 440 DEG C to 560 DEG C, and the treatment time ranges from 100 min to 150 min. According to the obtained high-performance copper alloy, the electric conductivity is larger than or equal to 79%, the Vickers hardness is larger than or equal to 148, and the tensile strength is larger than or equal to 584 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloys, and in particular to a high-performance copper alloy and a preparation process thereof. Background Art

[0002] Cu-Cr-Zr alloy is widely used in power, electronics, machinery and other fields due to its high strength, high conductivity, good heat resistance and ductility. This alloy is an important choice for the preparation of key materials such as high-speed railway contact wires, integrated circuit lead frames, heat exchanger elements and nuclear reactor components. It is also used in casting mold liners and shielding cladding in the International Thermonuclear Test Reactor. Due to its excellent performance, researchers continue to explore and improve its production process in order to further optimize the comprehensive performance of the alloy and expand its application range. In recent years, with the continuous development of industrial technology, the requirements for material performance are also constantly increasing, especially in the aerospace, automobile manufacturing, electronic information and other industries, the demand for high-performance copper alloys is growing. These industries require not only high electrical conductivity, but also excellent mechanical properties such as tensile strength, hardness and wear resistance. Therefore, it is particularly important to develop a high-performance Cu-Cr-Zr alloy that can meet these performance requirements at the same time.

[0003] In the existing technical means, in order to improve the strength and conductivity of Cu-Cr-Zr alloy, a solid solution aging treatment process is usually adopted. Specifically, a Cu-Cr-Zr alloy ingot is first obtained by smelting and casting, and then a solid solution treatment is performed on it to form a supersaturated solid solution of Cr and Zr elements in the copper matrix. Next, a large number of dislocations and vacancies are introduced through cold working such as cold rolling, which increases the number of atomic diffusion and nucleation sites and promotes more Cr precipitation. In addition, some researchers have tried to further optimize the microstructure of the alloy by adding trace elements or changing casting conditions. For example, adding trace amounts of Ag, Mg and other elements can refine the grains and enhance the toughness of the alloy. Another common method is to perform multi-stage aging treatment after solid solution treatment, that is, first perform low temperature aging treatment and then perform high temperature aging treatment to gradually improve the microstructure and properties of the alloy. Although these methods can improve the electrical conductivity and mechanical properties of the alloy to a certain extent, there are still some limitations in practical applications.

[0004] However, despite the use of the above-mentioned multiple means, the existing technology still finds it difficult to simultaneously achieve the goals of high strength and high conductivity of Cu-Cr-Zr alloys. In particular, after solution aging treatment, the tensile strength of the alloy still cannot meet the expected requirements (tensile strength is less than 400MPa). This shows that relying solely on a single aging strengthening and solid solution strengthening process cannot fully meet the demand for high-performance copper alloys in practical applications. The existence of these problems limits the widespread application of Cu-Cr-Zr alloys in high-end fields, especially in those industries that have strict requirements on material properties. Therefore, it is necessary to develop a new preparation process to overcome this problem in order to achieve the application and development of Cu-Cr-Zr alloys at a higher level. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a high-performance copper alloy and a preparation process thereof.

[0006] In a first aspect, the present application provides a preparation process of a high-performance copper alloy, comprising the following steps: S1, smelting and casting: Cu, Cr and Zr are mixed, smelted, and cast to obtain a Cu-Cr x -Zr y alloy ingot, x=0.5-0.7, y=0.1-0.19; S2, solid solution: the alloy ingot is subjected to solid solution treatment at a temperature of 900-960°C for 60-120min, and the solid solution heating rate is 8-15°C / min; S3, cold rolling: the cold rolling deformation is 40-80%; S4, aging: the alloy ingot after cold rolling is subjected to primary aging and secondary aging respectively, the treatment temperature of the primary aging is 150-160°C, the treatment time is 250-350min, and the treatment temperature of the secondary aging is 440-560°C, and the treatment time is 100-150min.

[0007] By adopting the above technical solution, the present invention first obtains the alloy Cu-Cr by smelting and casting. x -Zr yThe alloy ingot is then solution treated at a certain heating rate. At this time, the copper alloy has a certain electrical conductivity and mechanical strength. The present application then continues to perform cold rolling and controls the deformation amount of the cold rolling treatment, thereby increasing the number of dislocations and vacancies generated inside the copper alloy. At this time, the positions of atomic diffusion and nucleation also increase, the amount of Cr precipitation in the alloy system increases, and the electrical conductivity and Vickers hardness of the copper alloy are significantly improved; the present application then performs primary aging and secondary aging on the alloy. The primary aging can improve the plastic deformation ability of the alloy, and with the high temperature treatment of the secondary aging, the strength and plasticity of the alloy are significantly improved. The high-performance copper alloy finally obtained has both good electrical properties and mechanical properties. Experimental data show that its electrical conductivity is ≥79%, Vickers hardness is ≥148, and tensile strength is ≥584MPa.

[0008] In general, the preparation process of the present application includes smelting and casting, solution treatment, cold rolling and two aging treatments. The specific proportion of Cu-Cr-Zr alloy components (x=0.5-0.7, y=0.1-0.19) is melted and cast into an alloy ingot to ensure the uniform distribution of the basic alloy components. The solution treatment is carried out at 900-960°C for 60-120 minutes, and the heating rate is 8-15°C / min, so that the Cr and Zr elements are fully dissolved in the copper matrix to form a supersaturated solid solution, thereby improving the initial conductivity of the alloy. and mechanical strength, controlling the cold rolling deformation to 40-80%, increasing the dislocation density and the number of vacancies inside the alloy, promoting the subsequent Cr precipitation, and significantly improving the electrical conductivity and Vickers hardness of the alloy. The primary aging treatment is carried out at 150-160°C for 250-350 minutes to improve the plastic deformation ability of the alloy, making it more stable in subsequent processing. The secondary aging treatment is carried out at 440-560°C for 100-150 minutes to further improve the strength and plasticity of the alloy, so that the comprehensive performance of the final product reaches the best state.

[0009] Preferably, in step S1, x=0.6, y=0.15.

[0010] By adopting the above technical solution, the present application strictly controls the Cr content in the Cu-Cr-Zr alloy to 0.6 and the Zr content to 0.15, which can better balance the electrical conductivity and mechanical properties of the alloy. Specifically, when the Cr content is 0.6, a more uniform supersaturated solid solution can be formed during the solution treatment process, thereby improving the effect of subsequent cold rolling and aging treatment, and significantly improving the electrical conductivity of the alloy; at the same time, when the Zr content is 0.15, more fine dispersed phases can be promoted to precipitate during cold rolling and aging treatment. These fine dispersed phases can effectively hinder dislocation movement, thereby greatly improving the strength and hardness of the alloy. In the end, the high-performance copper alloy under this ratio exhibits excellent comprehensive performance.

[0011] Preferably, in step S2, the solution heating rate is 10°C / min.

[0012] By adopting the above technical scheme, the present application strictly controls the solid solution heating rate to 10°C / min, which can ensure the uniform distribution of alloy elements in the copper matrix and promote the formation of a more stable supersaturated solid solution. This not only helps to increase the number of dislocations and vacancies in the subsequent cold rolling process and increase the amount of Cr precipitation, thereby improving the conductivity and Vickers hardness of the copper alloy, but also ensures that the phase change during the aging treatment is more sufficient, so that the final high-performance copper alloy has higher tensile strength and good plasticity.

[0013] Preferably, in step S2, the alloy ingot is subjected to a solution treatment at a temperature of 950° C. for 110 minutes.

[0014] By adopting the above technical solution, the present application further controls the temperature and time of the solution treatment on the premise of controlling the solution heating rate, and performs a solution treatment on the alloy ingot at a temperature of 950°C for 110 minutes, so that the Cr and Zr elements are fully dissolved into the copper matrix to form a uniform supersaturated solid solution. This process not only increases the dislocation density generated in the subsequent cold rolling process and enhances the microstructural stability inside the alloy, but also promotes the effective precipitation of alloy elements during the subsequent aging treatment, significantly improving the electrical conductivity and mechanical properties of the alloy.

[0015] Preferably, in step S3, the cold rolling deformation is 60%.

[0016] By adopting the above technical solution, the application strictly controls the cold rolling deformation to 60%. At this time, the number of dislocations and vacancies generated inside the alloy increases significantly, and the positions of atomic diffusion and nucleation increase accordingly, which increases the amount of Cr precipitation and significantly improves the conductivity and Vickers hardness of the copper alloy. At the same time, this deformation can also effectively enhance the effect of subsequent aging treatment, so that the strength and plasticity of the alloy are significantly improved during the primary and secondary aging processes, and the high-performance copper alloy finally obtained has both good electrical and mechanical properties.

[0017] Preferably, in step S4, the primary aging treatment temperature is 155° C. and the treatment time is 300 min.

[0018] By adopting the above technical solution, the application sets the primary aging treatment temperature to 155°C and the treatment time to 300 minutes, which can significantly improve the plastic deformation ability of the alloy. This treatment condition makes the second phase particles inside the alloy more evenly distributed, reduces the movement of grain boundaries and dislocations, and thus improves the overall plasticity and toughness of the alloy. At the same time, the primary aging treatment also provides a better foundation for the subsequent secondary aging, which helps to further improve the strength and conductivity of the alloy.

[0019] Preferably, in step S4, the secondary aging treatment temperature is 525° C. and the treatment time is 120 min.

[0020] By adopting the above technical solution, the present application further controls the treatment temperature and treatment time of the secondary aging under the condition that the treatment temperature and treatment time of the primary aging have been strictly controlled. The treatment temperature is set to 525°C and the treatment time is 120 minutes, which can significantly improve the strength and plasticity of the alloy. Specifically, high-temperature aging under this treatment condition helps to further refine the precipitated phase and enhance its dispersion distribution effect, thereby effectively preventing the movement of grain boundaries and dislocations and greatly improving the tensile strength of the alloy. At the same time, the appropriate high-temperature treatment time ensures the effective release of the internal stress of the alloy and improves the overall uniformity and stability of the alloy.

[0021] In a second aspect, the present application provides a high-performance copper alloy produced by the above-mentioned preparation process, wherein the electrical conductivity of the high-performance copper alloy is ≥79%, the Vickers hardness is ≥148, and the tensile strength is ≥584 MPa.

[0022] In summary, this application has the following beneficial technical effects: 1. The present application significantly improves the electrical conductivity and Vickers hardness of the Cu-Cr-Zr alloy by combining solution treatment and cold rolling treatment. Specifically, the solution treatment causes the Cr and Zr elements to form a supersaturated solid solution in the copper matrix, while the cold rolling treatment increases the number of dislocations and vacancies, promoting more Cr precipitation, thereby making the electrical conductivity of the alloy reach more than 79% and the Vickers hardness reach more than 148; 2. The present application has been subjected to primary aging treatment and secondary aging high temperature treatment, which effectively improves the plastic deformation ability and strength of the alloy. The primary aging enhances the plastic deformation ability of the alloy, while the secondary aging further enhances the strength of the alloy, so that the tensile strength of the high-performance copper alloy finally obtained reaches more than 584MPa; 3. The preparation process of the present application not only solves the problem in the prior art that it is difficult to simultaneously achieve high conductivity and high strength, but also greatly improves the overall comprehensive performance of the alloy, making it more widely used in multiple fields such as electricity, electronics, and machinery. DETAILED DESCRIPTION

[0023] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0024] Example 1.1 A preparation process of a high-performance copper alloy comprises the following steps: S1. Melting and casting: High-purity Cu, high-purity Cr and high-purity Zr are melted in a vacuum high-frequency induction furnace, and then transferred to a vacuum single-roller rapid solidification device for casting, and the expression is Cu-Cr 0.5 -Zr 0.19 Alloy ingots; S2. Solid solution: The alloy ingot is heated under nitrogen protection at a solid solution heating rate of 8°C / min until the temperature in the system reaches 900°C, and the solid solution treatment lasts for 120 minutes; S3, cold rolling: cold rolling the alloy ingot obtained after solid solution, and controlling the cold rolling deformation to be 40%; S4. Aging: The cold-rolled alloy ingot is subjected to primary aging at 150°C for 350 min, and then subjected to secondary aging at 440°C for 150 min. Finally, high-performance copper alloy is obtained after cooling.

[0025] Example 1.2 A preparation process of a high-performance copper alloy comprises the following steps: S1. Melting and casting: High-purity Cu, high-purity Cr and high-purity Zr are melted in a vacuum high-frequency induction furnace, and then transferred to a vacuum single-roller rapid solidification device for casting, and the expression is Cu-Cr 0.7 -Zr 0.1 Alloy ingots; S2. Solid solution: The alloy ingot is heated under nitrogen protection at a solid solution heating rate of 15°C / min until the temperature in the system reaches 960°C, and the solid solution treatment is performed for 60 minutes; S3, cold rolling: cold rolling the alloy ingot obtained after solid solution, and controlling the cold rolling deformation to 80%; S4. Aging: The cold-rolled alloy ingot is subjected to primary aging at 160°C for 250 min, and then subjected to secondary aging at 560°C for 100 min. Finally, the high-performance copper alloy is obtained after cooling.

[0026] Example 2.1 A preparation process of a high-performance copper alloy, which is different from that of Example 1.1 in that, in step S1, the feed amounts of high-purity Cu, high-purity Cr and high-purity Zr are adjusted to obtain the expression Cu-Cr 0.6 -Zr 0.15 The alloy ingot is the same as that in Example 1.1.

[0027] Example 2.2 A preparation process of a high-performance copper alloy, which is different from that of Example 1.1 in that, in step S1, the feed amounts of high-purity Cu, high-purity Cr and high-purity Zr are adjusted to obtain the expression Cu-Cr 0.6 -Zr 0.19 The alloy ingot is the same as that in Example 1.1.

[0028] Example 2.3 A preparation process of a high-performance copper alloy, which is different from that of Example 1.1 in that, in step S1, the feed amounts of high-purity Cu, high-purity Cr and high-purity Zr are adjusted to obtain the expression Cu-Cr 0.5 -Zr 0.15 The alloy ingot is the same as that in Example 1.1.

[0029] Example 3.1 A preparation process of a high-performance copper alloy, which is different from Example 1.1 in that, in step S2, the solid solution heating rate is 10°C / min, and the rest is the same as Example 1.1.

[0030] Example 3.2 A preparation process of a high-performance copper alloy, which is different from Example 1.1 in that, in step S2, the solid solution heating rate is 12°C / min, and the rest is the same as Example 1.1.

[0031] Example 4 A preparation process of a high-performance copper alloy is different from that of Example 3.1 in that, in step S2, the alloy ingot is subjected to a solution treatment at a temperature of 950° C. for 110 min, and the rest is the same as that of Example 3.1.

[0032] Example 5.1 A preparation process of a high-performance copper alloy is different from that of Example 1.1 in that, in step S3, the cold rolling deformation is controlled to be 60%, and the rest is the same as that of Example 1.1.

[0033] Example 5.2 A preparation process of a high-performance copper alloy is different from that of Example 1.1 in that, in step S3, the cold rolling deformation is controlled to be 80%, and the rest is the same as that of Example 1.1.

[0034] Example 6 A preparation process of a high-performance copper alloy is different from that of Example 1.1 in that, in step S4, the treatment temperature of the primary aging is 155° C., the treatment time is 300 min, and the rest is the same as that of Example 1.1.

[0035] Example 7 A preparation process of a high-performance copper alloy is different from that of Example 6 in that, in step S4, the treatment temperature of the secondary aging is 525° C., and the treatment time is 120 min. The rest is the same as that of Example 6.

[0036] Comparative Example 1 The difference from Example 1.1 is that step S3 is removed, and the rest is the same as Example 1.1, specifically: S1. Melting and casting: High-purity Cu, high-purity Cr and high-purity Zr are melted in a vacuum high-frequency induction furnace, and then transferred to a vacuum single-roller rapid solidification device for casting, and the expression is Cu-Cr 0.5 -Zr 0.19 Alloy ingots; S2. Solid solution: The alloy ingot is heated under nitrogen protection at a solid solution heating rate of 8°C / min until the temperature in the system reaches 900°C, and the solid solution treatment lasts for 120 minutes; S3. Aging: The alloy ingot after solution treatment is subjected to primary aging at a temperature of 150°C for 350 min, and then subjected to secondary aging at a temperature of 440°C for 150 min. Finally, high-performance copper alloy is obtained after cooling.

[0037] Comparative Example 2 The difference from Example 1.1 is that in step S4, the primary aging is removed and the treatment time of the secondary aging is 500 min. The rest is the same as Example 1.1, specifically: S1. Melting and casting: High-purity Cu, high-purity Cr and high-purity Zr are melted in a vacuum high-frequency induction furnace, and then transferred to a vacuum single-roller rapid solidification device for casting, and the expression is Cu-Cr 0.5 -Zr 0.19 Alloy ingots; S2. Solid solution: The alloy ingot is heated under nitrogen protection at a solid solution heating rate of 8°C / min until the temperature in the system reaches 900°C, and the solid solution treatment lasts for 120 minutes; S3, cold rolling: cold rolling the alloy ingot obtained after solid solution, and controlling the cold rolling deformation to be 40%; S4. Aging: The cold-rolled alloy ingot is subjected to secondary aging at a temperature of 440° C. for 500 min, and finally cooled to obtain a high-performance copper alloy.

[0038] Performance Testing 1. The Vickers hardness of the high-performance copper alloy obtained in the embodiment and the comparative example was measured using a microhardness tester. Each sample was measured 10 times, and the maximum and minimum values ​​were discarded to take the average value. The load time was 15s, and the load force was 0.2N. The results are recorded in Table 1. 2. The conductivity of the high-performance copper alloy obtained in the embodiment and the comparative example at room temperature was studied using a digital metal conductivity meter. Each sample was measured 10 times, and the maximum and minimum values ​​were discarded to take the average value. The results are recorded in Table 1. 3. The high performance copper alloy obtained in the embodiment and the comparative example was subjected to room temperature tensile test, using a Shimadzu AG-XPLUS 100 kN universal testing machine, a tensile rate of 0.6 mm / min, and a dog-bone tensile specimen with a gauge size of 1 mm×4 mm×10 mm. To ensure the repeatability of the sample data, the sample in each state was subjected to two tensile tests. During the stretching process, a 10 mm contact extensometer was used to measure the tensile strength of the alloy, and the results are recorded in Table 1.

[0039] Table 1 Performance test table Group Vickers hardness Electrical conductivity % Tensile strength(MPa) Example 1.1 148 79.64 584 Example 1.2 149 79.20 586 Example 2.1 151 81.23 596 Example 2.2 149 79.34 588 Example 2.3 148 79.21 586 Example 3.1 150 80.39 593 Example 3.2 148 79.28 585 Example 4 152 84.38 597 Example 5.1 152 81.68 592 Example 5.2 148 79.46 587 Example 6 154 83.64 598 Example 7 156 86.95 607 Comparative Example 1 137 76.23 558 Comparative Example 2 142 78.01 570 Data Analysis: As can be seen from Table 1, the Vickers hardness of the high-performance copper alloy obtained in Examples 1.1-1.2 can reach 148-149, the conductivity can reach 79.20-79.64%, and the tensile strength can reach 584-586MPa, which proves that the present application improves the number of dislocations and vacancies generated inside the copper alloy through smelting and casting, solution treatment, cold rolling treatment and two different aging treatments. At this time, the positions of atomic diffusion and nucleation also increase, the amount of Cr precipitation in the alloy system increases, the conductivity and Vickers hardness of the copper alloy are significantly improved, and the plastic deformation ability and strength of the alloy are improved, so that the high-performance copper alloy finally obtained has both good electrical properties and mechanical properties; Embodiments 2.1-2.3 are different from Embodiment 1.1 in that, in step S1, the present application obtains alloy ingots with different expressions by adjusting the feeding amounts of high-purity Cu, high-purity Cr and high-purity Zr, wherein the Vickers hardness, electrical conductivity and tensile strength of the high-performance copper alloy obtained in Embodiment 2.1 are higher than those of other embodiments, proving that the present application controls the Cr content in the Cu-Cr-Zr alloy to 0.6 and the Zr content to 0.15, which can better balance the electrical conductivity and mechanical properties of the alloy. Specifically, when the Cr content is 0.6, a more uniform supersaturated solid solution can be formed during the solution treatment process, thereby improving the effects of subsequent cold rolling and aging treatment, and significantly improving the electrical conductivity of the alloy; at the same time, when the Zr content is 0.15, more fine dispersed phases can be promoted to precipitate during the cold rolling and aging treatment processes, and these fine dispersed phases can effectively hinder dislocation movement, thereby greatly improving the strength and hardness of the alloy; Embodiments 3.1-3.2 are different from Embodiment 1.1 in that, in step S2, the solid solution heating rate is different, and the Vickers hardness, electrical conductivity and tensile strength of the high-performance copper alloy obtained in Embodiment 3.1 are higher than those of other embodiments, which proves that the solid solution heating rate is controlled at 10°C / min in the present application, which can ensure the uniform distribution of alloy elements in the copper matrix and promote the formation of a more stable supersaturated solid solution, which not only helps to increase the number of dislocations and vacancies in the subsequent cold rolling process, increase the amount of Cr precipitation, thereby improving the electrical conductivity and Vickers hardness of the copper alloy, but also ensures that the phase change during the aging treatment is more sufficient, so that the high-performance copper alloy finally obtained has higher tensile strength and good plasticity; The difference between Example 4 and Example 3.1 is that in step S2, the time and temperature of the solution treatment are changed, and the Vickers hardness, electrical conductivity and tensile strength of the obtained high-performance copper alloy are improved, which proves that the present application further controls the temperature and time of the solution treatment on the premise of controlling the solution heating rate, and performs a solution treatment on the alloy ingot at a temperature of 950°C for 110 minutes, so that the Cr and Zr elements are fully dissolved into the copper matrix to form a uniform supersaturated solid solution. This process not only increases the dislocation density generated in the subsequent cold rolling process and enhances the microstructural stability inside the alloy, but also promotes the effective precipitation of alloying elements during the subsequent aging treatment, significantly improving the electrical conductivity and mechanical properties of the alloy. The difference between Examples 5.1-5.2 and Example 1.1 is that in step S3, the cold rolling deformation is different, and the Vickers hardness, electrical conductivity and tensile strength of the high-performance copper alloy obtained in Example 5.1 are higher than those of other examples, proving that the present application strictly controls the cold rolling deformation to 60%, thereby increasing the Cr precipitation amount, and significantly improving the electrical conductivity and Vickers hardness of the copper alloy. At the same time, the deformation can also effectively enhance the effect of subsequent aging treatment, so that the strength and plasticity of the alloy are significantly improved during the primary and secondary aging processes, and the high-performance copper alloy finally obtained has both good electrical and mechanical properties; The difference between Example 6 and Example 1.1 is that in step S4, the treatment temperature and treatment time of the primary aging are different, and the Vickers hardness, electrical conductivity and tensile strength of the high-performance copper alloy obtained in Example 6 are higher than those in Example 1.1, which proves that the application sets the primary aging treatment temperature to 155°C and the treatment time to 300min, which can significantly improve the plastic deformation ability of the alloy. This treatment condition makes the second phase particles inside the alloy more evenly distributed, reduces the movement of grain boundaries and dislocations, thereby improving the overall plasticity and toughness of the alloy. At the same time, the primary aging treatment also provides a better foundation for the subsequent secondary aging, which helps to further improve the strength and conductivity of the alloy. The difference between Example 7 and Example 6 is that in step S4, the treatment temperature and treatment time of the secondary aging are different, and the Vickers hardness, electrical conductivity and tensile strength of the high-performance copper alloy obtained in Example 7 are higher than those in Example 6, which proves that the present application further controls the treatment temperature and treatment time of the secondary aging under the condition that the treatment temperature and treatment time of the primary aging have been strictly controlled, which can significantly improve the strength and plasticity of the alloy. Specifically, the high-temperature aging under this treatment condition helps to further refine the precipitated phase and enhance its dispersion distribution effect, thereby effectively preventing the movement of grain boundaries and dislocations, and greatly improving the tensile strength of the alloy. At the same time, the appropriate high-temperature treatment time ensures the effective release of the internal stress of the alloy, and improves the overall uniformity and stability of the alloy. Comparative Example 1 is different from Example 1.1 in that the cold rolling step is removed, and the Vickers hardness, electrical conductivity and tensile strength of the obtained high-performance copper alloy are lower than those of Example 1.1, which proves that the cold rolling treatment of the present application can increase the number of dislocations and vacancies generated inside the copper alloy, and the positions of atomic diffusion and nucleation also increase accordingly, the amount of Cr precipitation in the alloy system increases, and the electrical conductivity and Vickers hardness of the copper alloy are significantly improved; The difference between Comparative Example 2 and Example 1.1 is that the primary aging treatment step is removed, and the Vickers hardness, conductivity and tensile strength of the obtained high-performance copper alloy are lower than those of Example 1.1, which proves that the primary aging and secondary aging of the present application complement each other and are indispensable, and together improve the electrical properties and mechanical properties of the high-performance copper alloy finally obtained.

[0040] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A process for preparing a high performance copper alloy, characterized in that: The following steps are involved: S1. Melting and casting: Cu, Cr and Zr are mixed, melted and cast to obtain the expression Cu-Cr x -Zr y Alloy ingot, x=0.5-0.7, y=0.1-0.19; S2. Solution treatment: subjecting the alloy ingot to solution treatment at a temperature of 900-960°C for 60-120 min, with a solution heating rate of 8-15°C / min; S3, cold rolling: cold rolling deformation is 40-80%; S4. Aging: The cold-rolled alloy ingot is subjected to primary aging and secondary aging respectively. The treatment temperature of the primary aging is 150-160° C., the treatment time is 250-350 min, and the treatment temperature of the secondary aging is 440-560° C., the treatment time is 100-150 min.

2. A process for preparing a high performance copper alloy according to claim 1, characterized in that: In the step S1, x=0.6, y=0.

15.

3. The process for preparing a high performance copper alloy according to claim 1, characterized in that: In step S2, the solution heating rate is 10°C / min.

4. A process for preparing a high performance copper alloy according to claim 3, characterized in that: In the step S2, the alloy ingot is subjected to a solution treatment at a temperature of 950° C. for 110 minutes.

5. The process for preparing a high performance copper alloy according to claim 1, characterized in that: In step S3, the cold rolling deformation is 60%.

6. The process for preparing a high performance copper alloy according to claim 1, characterized in that: In step S4, the primary aging treatment temperature is 155° C. and the treatment time is 300 min.

7. A process for preparing a high performance copper alloy according to claim 6, characterized in that: In step S4, the treatment temperature of the secondary aging is 525° C. and the treatment time is 120 min.

8. A high performance copper alloy obtained by the preparation process of the high performance copper alloy according to any one of claims 1 to 7, characterized in that: The electrical conductivity of the high-performance copper alloy is ≥79%, the Vickers hardness is ≥148, and the tensile strength is ≥584 MPa.

Citation Information

Patent Citations

  • Preparation method of cold deformation strengthened Cu-Cr-Zr-Mg alloy

    CN110373568A

  • Method for preparing CuCrZr alloy through two-stage aging process

    CN113832367A